Modo de vida e o manejo de açaizais nas várzeas do rio Mazagão, município de Mazagão-AP, Brasil - MATOS FILHO, João Ramos de (Universidade Federal do Pará, 2018)
The expansion of market interests established important changes in the lifestyle of coastal communities around the acai economy. The management of açai is an important economic activity and livelihood of coastal gatherers living in the floodplains of the Amazon estuary. However, the intensification of the fruit collection and indiscriminate removal of native species of management areas could cause significant environmental changes in the floodplains. Thus, the objective of this work was to study the lifestyle and their relationship with the native açai management systems of Foz de Mazagão Old community, Mazagão-AP municipality. The predominant vegetation in the community is presented in the form of floodplain forest. The extraction is a very important role in the community's diet, and fishing one of its main activities, together with selective logging, palm heart extraction and collection mainly açaí (Euterpe oleracea Mart.). In the field work was used the ethnographic method with participant observation techniques, formal and informal interviews. In the interviews structured to collect socioeconomic data and the lifestyle previously developed and tested forms were used, with open and closed questions, made orally and individually to people who responded the same way. A survey of the main resources used for the survival of community bordering Foz de Mazagão Old, main agricultural crops (fields), fruit (yard), timber, medicinal plants used, consumed fish and/or sold, bred animals, including others, through interviews using pre-designed forms. During visits to açai and open interviews with the owner, it was observed the management systems used and were classified into four types: intensive management, intermediate, moderate and without management. All of them were related to acai extraction dynamics, considering labor relations, as well as commercial agents and the circulation of açai. Through the crossing of this information was revealed that the market demand for the acai fruit is changing the lifestyle bordering Foz de Mazagão Old, prioritizing increasingly the activities related to the management and creating an increasing dependence of açai. Although the idea of sustainability of açai managed in the floodplains, a large-scale expansion of this practice in the riverine communities of Amapá State, as has occurred in Foz de Mazagão Old hides high environmental risks in the medium and long deadlines, mainly due to the completion of the deforestation "green", which do not use heat to promote torn down and a relative homogenization of vegetation in floodplains.